Dissecting the molecular mechanism of russeting in sand pear (Pyrus pyrifolia Nakai) by metabolomics, transcriptomics, and proteomics. (29th October 2021) - Shi, Chun‐Hui; Wang, Xiao‐Qing; Xu, Jian‐Feng; Zhang, Yu‐Xing; Qi, Baoxiu; Jun, Luo
Summary: Brown coloration and a rough appearance as russet and semi‐russet (partial russet) are features unique to the popular Asian sand pear ( Pyrus pyrifolia Nakai). The degree of russeting is different between different genotypes. Russeting is sensitive to water fluctuations, where excessive rainwater can trigger/stimulate its development. However, the molecular mechanism of russeting is currently unclear. Here, we employed multi‐omics, i.e., metabolomics, transcriptomics, and proteomics, and analyzed the effect of different sand pear genotypes and artificial rainfall on russeting of pear fruits. This led to the identification of 79, 64, and 29 differentially produced/expressed metabolites, transcripts, and proteins that are involved in the biosynthesis of suberin, phenylpropane, cutin, and waxes. Further analysis of these differentially expressed genes and their encoded proteins revealed that four of them exhibited high expression at both transcript and protein levels. Transient expression of one such gene, PbHHT1 (accession number 103966555), which encodes ω‐hydroxypalmitate‐ O ‐feruloyl transferase, in young green non‐russet fruits triggered premature suberization in the russeting pear genotypes. This coincided with increased production of 16‐feruloyloxypalmitic acid, a conjugated compound between phenols and esters during the polymerization for suberin formation. Collectively, our data from the combined three omics demonstrate that russeting in sand pear is a complex process involving the biosynthesis and transport of suberin and many other secondary metabolites. Significance Statement: Metabolomics, transcriptomics, and proteomics analysis demonstrates that russeting in sand pear fruit is a complex process involving the biosynthesis and transport of suberin and many other secondary metabolites. Transient expression of one of the identified genes, which encodes ω‐hydroxypalmitate‐ O ‐feruloyl transferase (HHT), triggered premature suberization in young green non‐russet sand pear fruit, which coincided with increased production of 16‐feruloyloxypalmitic acid, a conjugated compound between phenols and esters during the polymerization for suberin formation, indicating the important role of HHT in sand pear fruit russeting.